Impedance spectroscopic detection of binding and reactions in acid-labile dielectric polymers for biosensor applications. Issue 19 (3rd May 2018) - Dailey, Jennifer; Fichera, Michelangelo; Silbergeld, Ellen; Katz, Howard E.
Abstract : We synthesized previously unreported copolymers with cleavable acid-labile side chains for use as electrochemical sensing layers in order to demonstrate a novel architecture for a one-step immunosensor. Abstract : We synthesized previously unreported copolymers with cleavable acid-labile side chains for use as electrochemical sensing layers in order to demonstrate a novel architecture for a one-step immunosensor. This one-step system is in contrast to most antigen-capture signal amplification methods that involve complicated secondary labeling techniques, or require the addition of redox probes to achieve a sensing response. A series of novel copolymers composed of various trityl-containing monomers were synthesized and characterized to determine their dielectric properties. The results indicate that the thin films of these polymers are stable in water, but some begin to degrade under acidic conditions or upon antigen binding, causing observable changes in the phase angle.